Odin: Microsoft’s Scalable Fault-Tolerant CDN Measurement System - Calder, Matt; Schroder, Manuel; Gao, Ryan; Stewart, Ryan; Padhye, Jitu; Mahajan, Ratul; Ananthanarayanan, Ganesh; Katz-Bassett, Ethan (USENIX NSDI, 2018)
Content delivery networks (CDNs) are critical for delivering high performance Internet services. Using worldwide deployments of front-ends, CDNs can direct users to the front-end that provides them with the best latency and availability. The key challenges arise from the heterogeneous connectivity of clients and the dynamic nature of the Internet that influences latency and availability. Without continuous insight on performance between users, front-ends, and external networks, CDNs will not be able to attain their full potential performance. We describe Odin, Microsoft’s Internet measurement platform for its first-party and third-party customers. Odin is designed to handle Microsoft’s large user base and need for large-scale measurements from users around the world. Odin integrates with Microsoft’s varied suite of web-client and thick-client applications, all while being mindful of the regulatory and privacy concerns of enterprise customers. Odin has been operational for 2 years. We present the first detailed study of an Internet measurement platform of this scale and complexity.